Twelve tips for turning quality assurance data into undergraduate teaching awards: A quality improvement and student engagement initiative. (1st February 2017) - Newton, Kate; Lewis, Helen; Pugh, Mark; Paladugu, Madhavi; Woywodt, Alexander
Abstract: Data on teaching awards in undergraduate medical education are sparse. The benefits of an awards system may seem obvious at first glance. However, there are also potential problems relating to fairness, avoidance of bias, and alignment of the awards system with a wider strategy for quality improvement and curriculum development. Here, we report five- year single center experience with establishing undergraduate teaching awards in a large academic teaching hospital. Due to lack of additional funding we based our awards not on peer review but mainly on existing and very comprehensive quality assurance (QA) data. Our 12 tips describe practical points but also pitfalls with awards categories and criteria, advertising and disseminating the awards, the actual awards ceremony and finally embedding the awards in the hospital's wider strategy. To be truly successful, teaching awards and prizes need to be carefully considered, designed and aligned with a wider institutional strategy of rewarding enthusiastic educators.